Pengaruh Media Pembelajaran Interaktif Berbasis Powerpoint Terhadap Kecerdasan Visual Spasial Anak Usia 5-6 Tahun - Sofia, Ari; Afifah, Nada; Syafrudin, Ulwan (Universitas Muhammadiyah Metro, 2025)
The problem in this study can be seen from the child's lack of ability to understand the position of the image, understand the difference in color and understand the difference in size and the ability to solve simple problems, which can hinder the development of spatial visual intelligence. For this reason, teachers need to be more innovative in organizing learning using interesting and interactive media so that they can develop children's visual spatial intelligence. The purpose of this study is to determine the effect of the use of powerpoint-based interactive learning media on the spatial visual intelligence of children aged 5-6 years. This study is a quantitative research using a pre-experimental method with a one group pretest-posttest design. The research sample amounted to 27 children aged 5-6 years. Sampling was done using purposive sampling techniques. The observation data collection technique uses observation sheets by checking list. The instrument has been validated with a value of 0.336 – 0.861 after comparing it with the R table of 0.456 obtained 22 statements that were declared valid. The reliability test is 0.925. This shows that the instrument is valid and reliable. Then the data was analyzed using the Wilcoxon difference test. The results showed that there was an effect of the use of powerpoint-based interactive learning media on the spatial visual intelligence of children aged 5-6 years (Sig (2-tailed) p=0.00 (p<0.05) and Z=- 4.565). The Positive Ranks score for the mean Rank was 14 while the Sum of Ranks was 378.00. The findings of the study show that the use of powerpoint-based interactive learning media in learning can affect the spatial visual intelligence of children aged 5-6 years.